Guest-responsive metal-organic frameworks based on asymmetric bridging ligands - Bourne, Susan A.; Mehlana, Gift; Ramon, Gaëlle (International Union of Crystallography, 2016)
Guest-responsive metal-organic frameworks based on asymmetric bridging ligands